Analysis of Priority Scale for Post Hydrometeorological Disaster Housing Reconstruction in West Aceh Regency: Analisis Skala Prioritas Pembangunan Rumah Pasca Bencana Hidrometeorologi Kabupaten Aceh Barat - Hilma Erliana; Ade Dwinta; Cut Liliiza Yusra; Raina Parmitalia Dinda; Intan Wulan Sari (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2026)
Hydrometeorological disasters, such as the flash flood in West Aceh Regency in November 2025, caused severe damage to the houses of affected residents. This study aims to analyze economic, social, physical, and livability conditions and to establish post‑disaster housing intervention priorities. A quantitative descriptive method with percentage analysis was used on 187 affected households. Results show that 51.3% have very low income (<Rp500,000), 71.1% never save, 58.3% own no land, and 55.1% own no livestock. Social conditions are vulnerable: 40.1% have a very crowded room ratio, 54.5% have elderly/children under five, and 56.1% have low education level. Physical house conditions are severely damaged: leaky roofs (68.4%), poorly installed walls (65.2%), and weak floors (63.1%). Livability is very low: inadequate waste disposal (76.5%), fire hazards (70.1%), and structural hazards (69.0%). Based on the integration of the four variables, three priority levels for housing intervention were established: high priority (50 households) require total house reconstruction, medium priority (30 households) require heavy rehabilitation, and low priority (107 households) require light repairs. Given budget constraints, priority is given to the 50 households with the worst conditions. This study provides an objective basis for post‑disaster housing intervention priorities.